A computational study of vocal-ventricular fold coupling with glottal airflow simulation - Chan, Junheng (Nanyang Technological University, 2022)
This paper studied vocal-ventricular fold coupling (VVFC) with realistic glottal airflow. Previous research in the area had focused on the modelling of the vocal and ventricular folds and the use of forcing functions to obtain self-sustained oscillation. In this study, a proposed new model that can potentially be built in the three-dimensional biomechanical modelling software, ArtiSynth, is explored and detailed. This model sought to incorporate airflow simulated by the lattice Boltzmann method (LBM) into an existing model of the vocal and ventricular folds constructed with the finite-element method (FEM). The LBM implementation replaced the simple forcing function to produce a model that better simulated reality.